Stress Intensity Factors For A Crack In Bonded Dissimilar Materials Subjected To Various Stresses - K B Hamzah; N M A Nik Long; N Senu; Z K Eshkuvatov; M R Ilias (Horizon Research Publishing Corporation, 2024)
Indexed by WOS/SCOPUS/ERA